Medial Patellofemoral Ligament Reconstruction Using a Peroneus Longus Tendon Graft Case Report - Capalbo, José Victor Santos; Karakanian, Felipe Fuzita; Oliveira, Diego Escudeiro de; Campanha, David Bonini Vieira; Lima, Marcos Vaz de; Miranda, Lorena Morais; Jorge, Pedro Baches (Brazilian Journal of Case Reports, 2025)
Medial patellofemoral ligament (MPFL) reconstruction is commonly performed in the surgical treatment of patellar dislocation. In addition to conventional grafts, the peroneus longus (PL) tendon has also been efficiently used as an alternative. In this study, we describe the rare case of a patient with chronic patellar dislocation who underwent MPFL reconstruction using the PL tendon graft and anteromedialization of the tibial tuberosity. A 30-year-old male patient with a history of pain and instability in the left knee due to recurrent patellar dislocations over the past three years, previously treated conservatively. In the last month, he experienced an irreducible lateral patellar dislocation requiring open reduction, followed by another irreducible dislocation 20 days later. Physical examination and imaging revealed MPFL injury and a TT-TG distance of 22 mm. Open patellar reduction, MPFL reconstruction with part of the peroneus longus tendon, and tibial tuberosity anteromedialization were performed. After the usual preparation, the peroneus longus and brevis tendons were identified and isolated, and the former was harvested. Subsequently, patellar reduction and tibial tuberosity anteromedialization osteotomy were performed, followed by fixation of the PL graft at the anatomical femoral insertion point of the MPFL. After ligament reconstruction and osteotomy, the knee demonstrated satisfactory stability, with no dislocations during mobilization and no ankle pain complaints, while maintaining a preserved range of motion. Recent studies have shown favorable outcomes using the peroneus longus tendon in ligamentous knee reconstructions. Thus, the use of this tendon as a graft for MPFL reconstruction represents a viable and valuable alternative that should be mastered by orthopedic surgeons. A 30-year-old male patient with a history of pain and instability in his left knee due to recurrent patellar dislocations over the past 3 years was treated conservatively. In the last month, he suffered an irreducible lateral dislocation of the patella, requiring open reduction, and another irreducible dislocation occurred 20 days later. Physical and imaging examinations indicated a 22-mm MPFL and TGT lesion. Open reduction of the dislocation was performed, reconstruction of the MPFL with part of the long peroneal tendon and anteromedialization of the ATT. After the usual preparation, the long and short peroneal tendons were identified and isolated, and removed. Then, the patella was reduced and the ATT was anteromedialized osteotomy was performed, followed by fixation of the PL graft at the anatomical insertion point of the MPFL in the femur. After ligament reconstruction and osteotomy, the stability of the knee was satisfactory, with no dislocations during mobilization and no complaints of pain in ankle mobility, in addition to the preserved range of motion. Recent studies have shown good results with the use of the long peroneal tendon in knee ligament reconstructions. Therefore, the use of this as a graft for reconstruction of the medial patellofemoral ligament of the knee represents a viable and valuable alternative that should be mastered by the surgeon.